Jakość życia społeczności jeleniogórskiej - wyniki badań ankietowych - Bodak, Katarzyna; Dudek, Agnieszka; Kołodziejczak, Aneta (The Quality of Life of Inhabitants of Jelenia Góra - Results of Survey Research, 2007)
This paper is survey report and it has been written within the Project conducted by Pro Future, the Student Scientific Group of Economy and Public Administration. The survey was aimed at identification and assessment of the basic factors defining the quality of life of inhabitants of Jelenia Gora. The survey structure included questions concerning residential conditions, public health, recreation and refreshment, labour market, safety, transport, education, financial situation, natural environment, as well as problems and prospects for change affecting the quality of life.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 391-402